Kabbalistic Metaphors in Modeling the Environments of Life - Elena A. Korol (Corpus Mundi)
The article explores the role of mystical metaphors in the ways of constructing modern living environments. This research perspective is conditioned by the relevance of the problem of alienation in the urban environment, as well as the need to overcome this alienation in order to transform the city into a comfortable environment. The aspect of mystical metaphors in the context of the development of living environments, analysed in the article, points to the internal logic of the process of human habitation of living spaces. The internal dialectic of this process has been revealed: humans face a contradiction between the desire to settle and transform space and the impossibility of its final settlement due to the incomparable superiority of the environment over humans, which causes a feeling of alienation. The following conclusions are proposed: Kabbalistic metaphors offer a symbolic language for realising and describing both the experience of involved change in the world and alienation; innovations in the field of urban spaces revive ancient forms of human interaction with the living environment – the development and spread of media technologies, coupled with the user's limited knowledge of the principles of their functioning, are paradoxical in nature as a living environment for humans, combining the familiar and the transcendent, unexpectedly reproducing the logic of mystical tension between involvement and alienation; modern media technologies, with the general expansion of the boundaries of physicality and accepted living space, paradoxically bring the transcendent into the realm of everyday experience.